2012
DOI: 10.1089/lrb.2011.0015
|View full text |Cite
|
Sign up to set email alerts
|

Passive Pressure–Diameter Relationship and Structural Composition of Rat Mesenteric Lymphangions

Abstract: Background: Lymph flow depends on both the rate of lymph production by tissues and the extent of passive and active pumping. Here we aim to characterize the passive mechanical properties of a lymphangion in both midlymphangion and valve segments to assess regional differences along a lymphangion, as well as evaluating its structural composition. Methods and Results: Mesenteric lymphatic vessels were isolated and cannulated in a microchamber for pressure-diameter (P-D) testing. Vessels were inflated from 0 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 27 publications
7
52
0
Order By: Relevance
“…Interface 12: 20150280 circulation [13,34,35]. Loaded thicknesses in rat thoracic ducts reported in the literature are consistent with the present data [9,13]; geometric and functional parameters generally have large standard errors, suggesting large sample-to-sample variations. Similarly, others have used confocal microscopy to quantify angle orientation in bovine mesenteric lymphangions and report similar variability to that reported herein [12].…”
Section: Sample-to-sample Variations and Materials Heterogeneitysupporting
confidence: 90%
See 1 more Smart Citation
“…Interface 12: 20150280 circulation [13,34,35]. Loaded thicknesses in rat thoracic ducts reported in the literature are consistent with the present data [9,13]; geometric and functional parameters generally have large standard errors, suggesting large sample-to-sample variations. Similarly, others have used confocal microscopy to quantify angle orientation in bovine mesenteric lymphangions and report similar variability to that reported herein [12].…”
Section: Sample-to-sample Variations and Materials Heterogeneitysupporting
confidence: 90%
“…The mechanical environment probably contributes significantly to the overall contractile function of these vessels, leading some to study the relationship between intrinsic contractile function and mechanical cues such as magnitude and direction of flow, inlet and outlet pressure, or pressure gradient [3][4][5][6][7]. Also directly related to contractile function is the ability of the vessel to distend appropriately in response to mechanical loading, motivating studies that characterize the active and passive mechanical behaviour of lymphatic vessels [8][9][10][11]. Confocal microscopy has also been reported to characterize the vessel microstructure and geometry, which dictate the mechanical responses of the vessels [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of an optimum value of external pressure, at values slightly greater than inlet pressure p a , may explain why external compression as therapy for lymphedema works for only a small percentage of patients (28). However, recent experiments by Rahbar et al (19) showed that the vessel remains in its most compliant state over a wider range of diameters than is the case for the pressure-diameter relationship used in this study. Consequently, the range of optimal external pressures in vivo may be wider than that which we have shown here.…”
Section: Effect Of the Number Of Lymphangions In The Chainmentioning
confidence: 72%
“…Passive tension is dependent upon the connective tissue in the lymphatic wall, which contains an abundance of collagen and elastin fibers (Rahbar et al, 2012). Recent studies of the passive properties of rat mesenteric lymphatics showed that these vessels are compliant at the low intraluminal at which they typically operate (1–5 cm H 2 O).…”
Section: Luminal Pressure and Collecting Lymphatic Contractionsmentioning
confidence: 99%